Impact of Surgical Complexity on Health‐Related Quality of Life in Congenital Heart Disease Surgical Survivors. Issue 7 (July 2016) - O'Connor, Amy M.; Wray, Jo; Tomlinson, Ryan S.; Cassedy, Amy; Jacobs, Jeffrey P.; Jenkins, Kathy J.; Brown, Kate L.; Franklin, Rodney C. G.; Mahony, Lynn; Mussatto, Kathleen; Newburger, Jane W.; Wernovsky, Gil; et al.
Abstract : Background: Surgical complexity and related morbidities may affect long‐term patient quality of life (QOL). Aristotle Basic Complexity (ABC) score and Risk Adjustment in Congenital Heart Surgery (RACHS‐1) category stratify the complexity of pediatric cardiac operations. The purpose of this study was to examine the relationship between surgical complexity and QOL and to investigate other demographic and clinical variables that might explain variation in QOL in pediatric cardiac surgical survivors. Methods and Results: Pediatric Cardiac Quality of Life (PCQLI) study participants who had undergone cardiac surgery were included. The PCQLI database provided sample characteristics and QOL scores. Surgical complexity was defined by the highest ABC raw score or RACHS‐1 category. Relationships among surgical complexity and demographic, clinical, and QOL variables were assessed using ordinary least squares regression. A total of 1416 patient–parent pairs were included. Although higher ABC scores and RACHS‐1 categories were associated with lower QOL scores ( P <0.005), correlation with QOL scores was poor to fair ( r =−0.10 to −0.29) for all groups. Ordinary least squares regression showed weak association with R 2 =0.06 to R 2 =0.28. After accounting for single‐ventricle anatomy, number of doctor visits, and time since last hospitalization, surgical complexity scores added no additional explanation to the variance in QOL scores. Conclusions: ABC scores and RACHS‐1 categories are useful tools for morbidity and mortality predictions prior to cardiac surgery and quality of care initiatives but are minimally helpful in predicting a child's or adolescent's long‐term QOL scores. Further studies are warranted to determine other predictors of QOL variation.